Negotiation framework in Cascais real estate market - André, Daniel Mamede Bruno Ventura (2017)
Negotiation is such a broad field of knowledge with applications in different areas and sectors of activity. The purpose of this thesis is to investigate the negotiation framework in Cascais real estate market. This thesis considers the perspective of real estate professionals’ knowledge and behaviors attending negotiation concepts and approaches. The outcomes of a qualitative methodology result from twelve semi-structured interviews with twelve real estate professionals – General Director, Commercial Directors, Human Resources Director, Partner and Manager, Real Estate Agents, Senior Sales Consultant and Private Broker – of twelve different real estate companies from Cascais. There is a positive correlation with negotiation theory and reality. Real estate professionals are well aware of the main topics that are the basis of negotiation subject. Similarities and contrasts were found when compared information and studies presented in the literature review with the data analysis collected from the interviews. This thesis establishes some conclusions that contribute to the existing literature on negotiation framework in real estate market. It exposes how real estate professionals relate with negotiation theory and its involvement in their business, as well as their knowledge regarding negotiation theory.